DESIGN CONSIDERATIONS FOR DIGITAL IMAGE LIBRARIES PPT - Maeder, Anthony J. (My University, 2012)
Design of digital image libraries requires choices for numerous configuration aspects, such as resolution and display settings. These aspects can be categorized into different types of design criteria based on whether they are a human viewing and usage factor, or a stage in the image library management process. The criteria can also be applied in a hierarchy of nested versions of access to the library to suit different usage circumstances. Here we present a framework for design criteria using this approach, and apply it to some example cases.
Keywords: digital image, digitization, human visual system